An adolescent female having hepatocellular carcinoma associated with hepatitis B virus genotype H with a deletion mutation in the pre-S2 region. Issue 4 (April 2015) - Oba, Utako; Koga, Yuhki; Hoshina, Takayuki; Suminoe, Aiko; Abe, Kenji; Hayashida, Makoto; Taguchi, Tomoaki; Hara, Toshiro
Abstract: The genotypes of hepatitis B virus (HBV) have a distinct geographical distribution, with HBV genotype H being very rare in East Asia, including Japan. We herein report the case of a 12-year-old Japanese female with hepatocellular carcinoma (HCC) who exhibited HBV genotype H. Notably, the HBV isolated from the patient had a deletion mutation in the pre-S2 region. The genome of HBV genotype H in the patient with HCC has not been analyzed in detail. The deletion mutations in the pre-S2 region, which may play an important role in hepatocarcinogenesis in children, can also present in genotype H.